Laser cutting and welding tools for use in-bore on EU-DEMO service pipes - Keogh, Keelan; Kirk, Simon; Suder, Wojciech; Farquhar, Iain; Tremethick, Tristan; Loving, Anthony B. (Elsevier, 2018)
Replacement of blanket modules and divertor cassettes in the EU-DEMO will require rapid removal of hundreds of service pipes during maintenance downtime. Duration analysis of conventional joining processes, estimates cutting and welding would account for ∼60% of EU-DEMO remote maintenance. To minimize duration, laser cutting and welding tools have been developed for use within these pipes. The tools consist of a mechanical system to position the tool and the pipe correctly, and a miniaturized laser optics package to apply the process around the entire pipe circumference. Prototypes of the optics for the cutting and welding tools were produced, and the laser processing performances were assessed. Here, we will present the concept and prototype designs of the laser cutting and welding tools, the results of the prototype tool trials, and how the tools fit within the overall remote maintenance strategy for EU-DEMO, these results highlight the duration reduction of a laser process compared to conventional techniques, and the feasibility of a such a design for further development.
Keywords: EU-DEMO; Remote maintenance; Laser welding; Laser cutting; Service pipes